Silver and potassium incorporation in double-layer solution-processed Cu2ZnSnS4 solar cell - Ibrahim, Ahmad (2020)
Large open-circuit voltage (VOC) deficit has been widely regarded as the main hindrance to realize the full potential of the low-cost and environmental-friendly Cu2ZnSnS4 (CZTS) solar cell. Alloying and doping are seen as promising pathways to reduce the harmful defects in CZTS and the VOC deficit. In this study, we demonstrate the fabrication of double-layer CZTS alloyed with silver and doped with potassium (ACZTS-KCZTS). The device shows an increase in VOC relative to its corresponding Shockley–Queisser limit (VOC/VOC,SQ) and improvement of short-circuit current (JSC) compared to the CZTS reference to realize an optimized active area device efficiency of 8.24%. The avoidance of void formation and improved carrier collection in the bulk and interface region contributed to performance improvement. This double-layer configuration could be a viable route for codoping using other elements.